2018
DOI: 10.4236/ojpm.2018.82005
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Awareness Regarding Emergency Management of Epistaxis inside the School; Alahssa, Saudi Arabia

Abstract: Background: Epistaxis is one of the commonest emergencies encountered by ENT physicians as well as to family and emergency physicians. It is common among school children as they are easily injured during different school activities. Objective: The aim of this study was to assess the level of knowledge and attitude regarding first aid management of epistaxis among school teachers in Al-Ahsa, Saudi Arabia. Method: A cross sectional study was conducted in November 2017 among Saudi school teachers in AlAhssa regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 12 publications
4
4
3
Order By: Relevance
“…However, the result in our study is lower than other Saudi studies that claimed 54.5%, 68%, 94%, and 56% of their respondents had previously received information [24,25,27,28]. Our results were that about half of our participants had taught students with epistaxis during their careers, which is higher than the results of an online study conducted in Saudi Arabia, which found 41.9% had encountered epistaxis in students, but it was lower than the experience of study participants from other regions of Saudi Arabia, including Riyadh (68.1%), Al Ahsa (67%), Aseer (72.6%), and Taif (66.6%) [24][25][26][27][28]. Almost two-thirds of our participants were aware that with epistaxis, they must try to stop the bleeding, which is a lower percentage than in the studies conducted by Alshehri et al, which showed 68% of their participants knew this and Al-Kubaisy et al, which reported 76.5% of their participants were aware of this fact [24,25].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the result in our study is lower than other Saudi studies that claimed 54.5%, 68%, 94%, and 56% of their respondents had previously received information [24,25,27,28]. Our results were that about half of our participants had taught students with epistaxis during their careers, which is higher than the results of an online study conducted in Saudi Arabia, which found 41.9% had encountered epistaxis in students, but it was lower than the experience of study participants from other regions of Saudi Arabia, including Riyadh (68.1%), Al Ahsa (67%), Aseer (72.6%), and Taif (66.6%) [24][25][26][27][28]. Almost two-thirds of our participants were aware that with epistaxis, they must try to stop the bleeding, which is a lower percentage than in the studies conducted by Alshehri et al, which showed 68% of their participants knew this and Al-Kubaisy et al, which reported 76.5% of their participants were aware of this fact [24,25].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, onequarter of the participants were aware that first aid for epistaxis includes the application of compression on the cartilaginous part of the nose, but only a few (3.6%) knew the correct compression time of more than 10 minutes. This finding is in agreement with other Saudi studies that showed 23% and 25% awareness levels, respectively, but their reported levels of knowledge about compression time were a bit higher than ours at 12.8% and 7%, respectively [24,25]. Other studies have reported 27.4%, 30%, 29.1%, and 64.6% of participants had awareness of compression on the cartilaginous part of the nose, and the correct compression time was reported among 11.9% and 10.1% of participants in other studies [26,28,33,34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Data was collected using a pre-tested and semi-structured interviewer administered questionnaire that is developed based on a previous study. 3,7,14,[18][19][20][21][22][23][24][25][26] The questionnaire was first prepared in English and translated to local language (Amharic) for the data collection. The question was back-translated to English to check its consistency.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
“…12 This makes the problem mostly ignored, and results in limited awareness in society on emergency first aid management of the disease. 25 It is unclear how much the level of epistaxis is and which factors locally are associated to the case. Basically the distribution of epistaxis is common among young adults.…”
Section: Introductionmentioning
confidence: 99%